Challenging the new orthodoxy: a critique of SPLISS and variable-oriented approaches to comparing sporting nations. Issue 4 (7th August 2020) - Henry, Ian; Dowling, Mathew; Ko, Ling-Mei; Brown, Phil
ABSTRACT: Research Question : In recent years the comparative sport policy field has become dominated by the 'SPLISS' approach developed by De Bosscher and colleagues. While this approach has developed important insights into the statistical relationship between key groups of independent variables and indicators of elite sport policy success, nevertheless its attempts to identify and explain both statistical association and causal relationships have significant limitations. The paper thus seeks to address the question of the nature of such strengths and limitations and their implications for theory, policy and practice. Methods: As a review paper it develops a critical evaluation of claims made for the SPLISS approach to variable oriented comparative policy analysis. Results: The paper identifies and focuses on the implications of six key problems for the SPLISS approach, namely: philosophical assumptions and causal variables; the black box problem; internal validity issues; non-equivalence and reliability; the neglect of agency; and misconceptions in the use of mixed methods. Implications : The paper's findings represent a challenge to the hegemony of this variable-oriented approach and they argue not for replacement or rejection of such an approach, but for recognition of its limitations, and of the opportunities for complementing it with case-driven, qualitative analysis generating causal accounts of policy outcomes.